Respuesta :
Answer:
[tex]x=-3\\x=6[/tex]
Step-by-step explanation:
We begin with [tex]x^2-3x-18=0[/tex]
To factor this, we need to look for two things:
Two numbers that add together to get [tex]-3[/tex] and two numbers that multiply together to get [tex]-18[/tex].
One method to find the answer is to write out each of the solutions to the multiplication and then check the sum of each of those digits:
The numbers that multiply together to get [tex]-18[/tex] are:
1 and -18
-1 and 18
2 and -9
-2 and 9
3 and -6
-3 and 6
Now, we can add each of these pairs of digits together to find which one gives us an answer of [tex]-3[/tex]
[tex]1+(-18)=-17\\\\-1+18=17\\\\2+(-9)=-7\\\\-2+9=7\\\\3+(-6)=-3\\\\-3+6=3[/tex]
From this, we can see that 3 and -6 gave us the result of -3. This means that these are the two factors.
To get our answer from this, we need to put our answer in the form of [tex](x+a)(x+b)=0[/tex]
This gives us the factored form of [tex](x+3)(x-6)=0[/tex]
To solve this equation, we must make either parenthesis equal to zero. This means that our solutions will be
[tex]x=-3\\x=6[/tex]